2016
DOI: 10.1371/journal.pone.0152724
|View full text |Cite
|
Sign up to set email alerts
|

Airway Microbiota in Severe Asthma and Relationship to Asthma Severity and Phenotypes

Abstract: BackgroundThe lower airways harbor a community of bacterial species which is altered in asthma.ObjectivesWe examined whether the lower airway microbiota were related to measures of asthma severity.MethodsWe prospectively recruited 26 severe asthma, 18 non-severe asthma and 12 healthy subjects. DNA was extracted from induced sputum and PCR amplification of the V3-V5 region of bacterial 16S rRNA gene was performed.ResultsWe obtained 138,218 high quality sequences which were rarefied at 133 sequences/sample. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
136
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(152 citation statements)
references
References 48 publications
(70 reference statements)
8
136
4
4
Order By: Relevance
“…Recently, it has been shown that the dysbiosis of the lower airway microbiome correlates with clinical characteristics of chronic persistent asthma, including airflow obstruction, use of corticosteroid medications, and presence of airway eosinophilia [93,94]. This suggests that the composition of the airway microbiome may be important in severe eosinophilic asthma, and as such might become a unique biomarker in the future.…”
Section: Genetic Markers Cell-surface Markers and Microbiomementioning
confidence: 99%
“…Recently, it has been shown that the dysbiosis of the lower airway microbiome correlates with clinical characteristics of chronic persistent asthma, including airflow obstruction, use of corticosteroid medications, and presence of airway eosinophilia [93,94]. This suggests that the composition of the airway microbiome may be important in severe eosinophilic asthma, and as such might become a unique biomarker in the future.…”
Section: Genetic Markers Cell-surface Markers and Microbiomementioning
confidence: 99%
“…This is contrary to findings in the gut microbiota, in which chronic inflammatory disorders are associated with bacterial diversity depletion (16), and indicates that, at least for asthma, the nature of microbiota perturbation associated with this chronic inflammatory disease lies in its difference from the healthy microbial state in that specific niche. An independent study of induced sputum from 56 adults, including 26 individuals with severe asthma, indicated that enrichment of specific Streptococcus taxa is associated with recentonset asthma, rhinosinusitis, and sputum eosinophilia (23). Independently, Huang and colleagues demonstrated that the bronchial bacterial community composition in those with severe asthma (n = 40) was related to body mass index, sputum total leukocytes, and bronchial biopsy eosinophil numbers, with each of these factors associated with distinct airway bacterial community compositions (22).…”
Section: Relationships To Diseases Of the Lungs And Airwaysmentioning
confidence: 99%
“…Analyses of 16S rRNA have found that the airway hosts a complex community of microbes; moreover, bacterial populations of asthmatic patients are unlike those of healthy control subjects 2728. The bacterial compositions of bronchial samples have also exhibited differences between 2 groups 2930.…”
Section: Introductionmentioning
confidence: 99%